Aspectos fisiológicos e bioquímicos da tolerância induzida por bioestimulante em variedades de feijão-caupi sob déficit hídrico - Silva, Johny de Souza (2023)
Climate change has emerged as a critical challenge in the 21st century, significantly impacting agriculture, particularly cowpea cultivation. Rising temperatures, unpredictable rainfall patterns, and extreme weather events threaten food security. Biostimulants, such as seaweed extracts and fulvic acids, have become promising alternatives for alleviating water scarcity in plants by stimulating various processes, including root growth, antioxidant defense activation, and osmoregulation. Furthermore, metabolomic analysis provides a detailed insight into these responses. Given the significance of cowpea in arid and semi-arid regions, such as the Brazilian Northeast, it becomes essential to comprehend cowpea's responses to drought and the potential influence of biostimulant use as a management strategy to mitigate adverse effects on productivity. Consequently, this study aimed to investigate the effect of biostimulant application on morphological, physiological, and biochemical changes, as well as the modulation of primary metabolites in two cowpea varieties grown under water deficit conditions. Two experiments were conducted. The first experiment involved a 2x2 factorial arrangement (two water conditions: with and without water deficit x biostimulant application management: with and without biostimulant) with repeated measurements over time, followed by rehydration after nine days of progressive drought. The second experiment adopted a completely randomized design in a 3x2x2 factorial arrangement, considering three soil water conditions: irrigated control, moderate drought, and severe drought; two genotypes: Pingo de Ouro 1.2 – PO and Sempre-verde – SV; and two biostimulant treatments: with biostimulant – CB and without biostimulant – SB. Various parameters were assessed, including plant length, dry mass, gas exchange, chlorophyll a fluorescence, malondialdehyde (MDA) and proline content, electrolyte leakage, relative water content (RWC), antioxidant enzyme activity, productivity variables, and, finally, leaf metabolic profiling. In both experiments, water deficit significantly affected several cowpea plant characteristics. However, the biostimulant had a positive impact on photosynthetic efficiency in plants subjected to moderate water deficit, mitigating membrane damage, electron transport rate, and instantaneous carboxylation efficiency. Additionally, a positive association was observed between biostimulant application and the enzymatic defense system. The leaf metabolic profile of the evaluated genotypes exhibited differential tolerance to water deficit, with greater alterations observed in the Sempre-verde genotype. It is worth noting that rehydration of plants, simulating a dry spell situation, prompted positive responses, particularly in plants treated with the biostimulant. This demonstrates the ability of biostimulant-treated plants to recover after drought, an important aspect to consider in breeding programs. In conclusion, the use of biostimulant based on Ascophyllum nodosum and fulvic acids (FH Attivus®) appears to be a promising strategy to assist cowpea in adapting to unfavorable conditions of water scarcity